DEVELOPING DEVICES FOR CURRICULUM DEVELOPMENT AND LEARNING BIOLOGY COURSE BASED ON LENTERA OF MOODLE LEARNING MANAGEMENT SYSTEM AT UIN ALAUDDIN MAKASSAR - Rapi, Muhammad; Hasanah, Ummul; Hijriah, Nurul Sakinah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: This study aims to develop valid, practical, and effective lecture devices based on Lentera application of Moodle Learning Media System (LMS) for Curriculum Development and Learning course. The research type used was development research with the Plomp development model, consisting of phases 1) preliminary investigation, 2) design, 3) realization/construction, and 4) test, evaluation & revision. The research subjects were 29 students of the fourth semester of Biology Education Study Program (2019/2020). The instruments used in data collection are validation sheets, practicality questionnaires, and learning outcomes tests. The test results indicated valid, practical, and effective products. Therefore, the development product in this research can be used to accommodate students’ learning in Curriculum Development and Learning Biology course. Abstrak: Penelitian ini bertujuan untuk mengembangkan perangkat perkuliahan berbasis aplikasi LMS Moodle Lentera pada matakuliah Pengembangan Kurikulum dan Pembelajaran yang valid, praktis, dan efektif. Jenis penelitian menggunakan model pengembangan Plomp, yang terdiri atas fase 1) preliminary investigation, 2) design, 3)realization/construction, dan 4) test, evaluation & revision. Subjek penelitiannya adalah 29 orang mahasiswa Prodi Pendidikan Biologi semester 4 (2019/2020). Instrumen yang digunakan dalam pengumpulan data yaitu lembar validasi, angket kepraktisan, dan tes hasil belajar. Hasil uji menghasilkan produk yang valid, praktis, dan efektif. Dengan demikian, produk pengembangan pada penelitian ini dapat digunakan dalam mengakomodasi pembelajaran mahasiswa pada matakuliah Pengembangan Kurikulum dan Pembelajaran Biologi.